Impact of the COVID-19 pandemic on core surgical training. Issue 4 (November 2020) - Khan, Khurram Shahzad; Keay, Rona; McLellan, Morag; Mahmud, Sajid
Background and aims: COVID-19 pandemic has caused significant disruption in training which is even more pronounced in the surgical specialties. We aim to assess the impact of COVID-19 pandemic on core surgical training. Methods: All core surgical and improving surgical trainees in West of Scotland region were invited to participate in an online voluntary anonymous survey via SurveyMonkey. Results: 28 of 44 (63.6%) trainees responded, 15 (53.6%) were CT1/ST1. 14 (50.0%) working in teaching hospital and 15 (53.6%) working in general surgery. 20 (71.4%) felt that due to the pandemic they have less opportunity to operate as the primary surgeon. 21 (75.0%) have not attended any outpatient clinics. 8 (28.6%) did not have any form of access to the laparoscopic box-trainer. 20 (71.4%) felt their level of confidence in preforming surgical skills has been negatively impacted. 18 (64.3%) found it difficult to demonstrate progress in portfolio. 21 (75.0%) trainees have not attended any teaching. 10 (35.7%) trainees have been off-sick. 8 (28.6%) trainees have felt slightly or significantly more stressed. Conclusion: COVID-19 pandemic has an unprecedented negative impact on all aspects of core surgical training. The long term impact on the current cohort of trainees is yet to be seen.